The future of scholarship on diversity and inclusion in organizations - King, Eden B.; Roberson, Quinetta M.; Hebl, Michelle R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"The current volume, the fourth in the series, provides a broad look at the meaning and understanding of diversity and inclusion in organizations. The contributors to this book look toward the future of D&I in organizations and the scholarship of these phenomena. This future focus references not only the content of the chapters-- which we hoped would offer new ideas, emphases, theories, and predictions-- but also to the contributors, emerging scholars who are the future of the field. Indeed, the chapters in this volume offer new perspectives on diversity in organizations, problematize existing perceptions and practices, and offer potential directions for change. Together, the questions and ideas offered these chapters generate a path forward for a thoughtful and nuanced view of D&I in future organizational science. In spite and because of their critiques of the status quo, the scholars and scholarship highlighted here provide hope for positive change"-- Provided by publisher.
Keywords: Diversity in the workplace.; Marginality, Social.; Multiculturalism.; Minorities.; Social justice.; Management.; Organization.; Business & Economics -- Diversity & Inclusion.; Diversity, equality and inclusion in the workplace.; elektronické knihy; electronic books